The legend of Korra. Ruins of the empire. Part three - DiMartino, Michael Dante; DiMartino, Michael Dante; Konietzko, Bryan (Dark Horse Books, 2020)
Kuvira's true nature is revealed and the Earth Kingdom will feel the consequences.